Stereotypes and madrassas: Experimental evidence from Pakistan - Adeline Delavande; Basit Zafar (Federal Reserve Bank of New York, 2011)
Madrassas (Islamic religious seminaries) have been alleged to be responsible for fostering Islamic extremism and violence, and for indoctrinating their students in narrow worldviews. However, we know very little about the behavior of Madrassa students, and how other groups in their communities interact with them. To investigate this, we use unique experimental and survey data that we collected in Madrassas and other educational institutions in Pakistan. We randomly match male students from institutions of three distinct religious tendencies and socioeconomic background - Madrassas, Islamic Universities, and Liberal Universities - and observe their actions in several experiments of economic decision-making. First, we find a high level of trust among all groups, with students enrolled at Madrassas being the most trusting and exhibiting the highest level of unconditional other-regarding behavior. Second, within each group, we fail to find evidence of in-group bias or systematic out-group bias either in trust or tastes. These findings cast doubt on the general perception that Madrassas teach hatred and narrow worldviews. Third, we find that students of Liberal Universities underestimate the trustworthiness of Madrassa students, suggesting that an important segment of the society has mistaken stereotypes about students in religious seminaries.
Keywords: C90; C70; Z12; 330; trust; group identity; religious seminaries; unconditional other-regarding behavior; expectations